2021
DOI: 10.1111/hepr.13699
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategies for the early diagnosis of hepatitis B virus reactivation

Abstract: Hepatitis B virus (HBV) reactivation under systemic chemotherapy or immunosuppressive therapy is a serious complication among HBV‐resolved patients. Some medications, such as more than 2 weeks of corticosteroid therapy, can influence HBV reactivation; therefore, screening tests that measure hepatitis B surface antigen (HBsAg), hepatitis B core antibody, and hepatitis B surface antibody before therapy are required. Additionally, because HBV reactivation has been reported in patients positive for HBsAg treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 67 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…More recently, Inoue et al have reported that a fully automated, high-sensitivity CLEIA for HBcrAg detection (iTACT-HBcrAg; Fujirebio Corporation, Tokyo, Japan) is useful for the management of HBV reactivation and of HBeAg-negative CHB patients [ 95 , 96 ]. The iTACT-HBcrAg assay is inexpensive and simpler to use than the HBV DNA assay, and provides results within 30 min.…”
Section: Drug Discovery Study Aimed At Hbvmentioning
confidence: 99%
“…More recently, Inoue et al have reported that a fully automated, high-sensitivity CLEIA for HBcrAg detection (iTACT-HBcrAg; Fujirebio Corporation, Tokyo, Japan) is useful for the management of HBV reactivation and of HBeAg-negative CHB patients [ 95 , 96 ]. The iTACT-HBcrAg assay is inexpensive and simpler to use than the HBV DNA assay, and provides results within 30 min.…”
Section: Drug Discovery Study Aimed At Hbvmentioning
confidence: 99%
“…However, before the use of MSCs in AVH patients, reducing the risk of self-infection with MSCs and whether the immunosuppressive effect of MSCs impairs the body's ability to clear the virus, leading to persistent or chronic viral infection, as well as affecting the therapeutic efficacy of antiviral drugs, need to be further investigated. In patients with oncologic and autoimmune diseases complicated by chronic viral infections, viral reactivation has been reported after the use of some drugs, such as corticosteroid therapy and immune checkpoint inhibitors (ICIs) for more than 2 weeks [ 464 ], and viral reactivation significantly increases the risk of acute liver failure and death [ 465 ]. It is worthwhile to investigate when and how MSCs can be applied to strike a balance between antiviral immunity and mitigation of liver pathological damage.…”
Section: Mscs For Inflammatory Liver Diseasesmentioning
confidence: 99%
“…More recently, Inoue et al demonstrated that a fully automated, high-sensitivity CLEIA for HBcrAg detection (iTACT-HBcrAg; Fujirebio, Inc., Tokyo, Japan), is about 10-fold more sensitive than the conventional HBcrAg assay, and is even more useful for monitoring transcriptional activity of cccDNA and detecting HBV reactivation before the onset of hepatitis [ 98 , 99 ]. Since iTACT-HBcrAg does not require any special technology and provides results within 30 min; it is expected to be used in clinical practice and research in the future.…”
Section: Hbcragmentioning
confidence: 99%